1998
DOI: 10.1128/aac.42.11.3014
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Clindamycin and Its Metabolite N -Demethylclindamycin into Cerebrospinal Fluid following Intravenous Infusion of Clindamycin Phosphate in Patients with AIDS

Abstract: Clindamycin, which is usually used in combination with pyrimethamine, has been proven effective in the treatment of cerebral toxoplasmosis in human immunodeficiency virus-infected patients. However, it is not known if clindamycin achieves inhibitory concentrations at the site of infection. Also, it has been hypothesized that the activity of clindamycin against Toxoplasma gondiimay be due, at least in part, to a metabolite. We evaluated the penetration of clindamycin and its major metabolite,N-demethylclindamyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…It has been suggested that time-dependent antimicrobial agents should remain above the MIC of pathogens for at least three malaria cycle of seven days. Unlike fosmidomycin, recent studies have suggested that clindamycin displays concentration-dependent bacteriocidal activity [17,29] while exhibiting an in vitro post antibiotic effect (PAE) for certain period. In vivo , the PAE is generally longer and due to effects such as post antibiotic leukocyte enhancement and post-antibiotic sub-MIC effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that time-dependent antimicrobial agents should remain above the MIC of pathogens for at least three malaria cycle of seven days. Unlike fosmidomycin, recent studies have suggested that clindamycin displays concentration-dependent bacteriocidal activity [17,29] while exhibiting an in vitro post antibiotic effect (PAE) for certain period. In vivo , the PAE is generally longer and due to effects such as post antibiotic leukocyte enhancement and post-antibiotic sub-MIC effect.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded data obtained using microbiologic assay techniques that may not have reliably distinguished clindamycin from clindamycin metabolite concentrations. To provide the concentration time data for the adult PBPK model development, we selected 3 adult clindamycin PK studies that were most appropriate based on route of administration, study participant demographics and clinical characteristics, and bioanalytical method used (Supplementary Table 1) (13-15). We used the software Plot Digitizer® (version 2.6.6) to extract the concentration versus time data.…”
Section: Methodsmentioning
confidence: 99%
“…In that study, 8 of 49 patients experienced dose-limiting toxic effects, most commonly rash. Gutti et al looked at penetration of clindamycin and its metabolite into cerebrospinal fluid in AIDS patients, and found that the concentrations of clindamycin in CSF are well above the 50% inhibitory concentrat io n of 0.0 01 m g p er lite r and the para sit i cidal concentration of 0.006 mg per liter [28].…”
Section: Therapymentioning
confidence: 99%